2012
DOI: 10.3171/2012.9.focus12252
|View full text |Cite
|
Sign up to set email alerts
|

Application of an aviation model of incident reporting and investigation to the neurosurgical scenario: method and preliminary data

Abstract: Object Incident reporting systems are universally recognized as important tools for quality improvement in all complex adaptive systems, including the operating room. Nevertheless, introducing a safety culture among neurosurgeons is a slow process, and few studies are available in the literature regarding the implementation of an incident reporting system within a neurosurgical department. The authors describe the institution of an aviation model of incident reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…CQC patient survey results are outcome factors commonly used to characterize institutions. [ 35 , 41 , 42 ] With respect to using CQC patient survey results there is potential for bias in relying on the patient’s perception of care. Patients may over-estimate safety within an institution as they are not necessarily aware of safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…CQC patient survey results are outcome factors commonly used to characterize institutions. [ 35 , 41 , 42 ] With respect to using CQC patient survey results there is potential for bias in relying on the patient’s perception of care. Patients may over-estimate safety within an institution as they are not necessarily aware of safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little information in the literature that reviews neurosurgical error in the format described by the RCA committees. Ferroli and his team in Italy have published one of the few reports that attempted to analyse neurosurgical error by applying an incident‐reporting model in the neurosurgical operating theatre using the expertise of an aviation system expert . They found that few studies were available to them regarding the implementation of an incident‐reporting system within a neurosurgical department.…”
Section: Discussionmentioning
confidence: 99%
“…A research study suggested that in order for this aviation style reporting process to work effectively, all the people involved should be within the same institution. 5…”
Section: Aviation Mode Of Incident Reportingmentioning
confidence: 99%